IL28B SNPs rs12979860 and rs8099917 Are Associated with Inflammatory Response in Argentine Chronic HCV Patients - Machicote, Andrés Pablo (2018)
Background: Hepatitis C virus (HCV) is a major cause of chronic liver disease,including cirrhosis and liver cancer. The aim of our study was to determinewhether IL28B single nucleotide polymorphisms (SNPs) rs12979860 andrs8099917 can be considered a prognostic host factor in untreated chronicHCV patients. Methods: We set up a real-time Allele Specific PCR amplificationto determine the allele present in each polymorphic site, and statisticallygrouped and compared this result with clinical data. Results: We determinedrs12979860 and rs8099917 genotype and allele frequencies in a single cohortof untreated chronically HCV-infected patients. We found significant associations between higher inflammatory activity, measured as ALT levels orMETAVIR scores and rs12979860 CC (P = 0.0013 and P = 0.0033, respectively)and rs8099917 TT (P = 0.0005 and P = 0.0264, respectively) genotypes. Interestingly,considering both genotypes together, we also found associationwith ALT levels (P = 0.0003; OR = 5.125) or METAVIR scores (P = 0.0038;OR = 5.179), suggesting and additive effect on liver inflammation in these patients. Conclusion: we show association between hepatic inflammatory activityin a single Argentinean untreated chronically HCV cohort and SNPs locatedin the interferon lambda gene region. The studied polymorphisms, togetherwith further innate and adaptive immune responses, clearly play a rolein modulating the HCV infected patients outcome, contributing to hepatic inflammation and possible fibrosis/cirrhosis.